COMPARISON OF FUNCTIONAL CAPACITY VALUES MEASURED BY SIX MINUTES WALK TEST (6MWT) IN CHRONIC OBSTRUCTIVE LUNG PATIENTS ACCOMPANIED - Nazif Fuadi Noer*, Ali N. Nasution, Nizam Akbar, Anggia C. Lubis, Hilfan A. P Lubis, Harris Hasan (International Journal of Research Science and Management, 2020)
Introduction: Chronic Obstructive Pulmonary Disease is still the leading cause of mortality in the world. Increased pulmonary pressure and hypoxemia in COPD cause impaired left ventricular diastolic function. Impaired respiration accompanied by cardiovascular disorders can cause a decrease in activity ability. Functional capacities that describe the ability of activities can be assessed by the 6 minute walk test. The purpose of this study was to assess the comparison of functional capacity values in COPD patients with or without diastolic disorders. Method: This study is a cross-sectional analytic study involving 88 subjects who met the inclusion criteria. Patients were grouped according to the severity of COPD and the presence of diastolic dysfunction assessed by echocardiography. Cardiac training was performed in all test groups. Data analysis uses bivariate analysis to determine comparisons on categorical variables followed by multivariate analysis to determine comparisons between test groups. Results: Of a total of 88 patients, there were 28 patients (31%) with mild COPD without diastolic dysfunction, there were 16 patients (18%) with mild COPD accompanied by diastolic dysfunction, 15 patients (17%) with severe COPD without diastolic dysfunction, 29 patients (32%) with severe COPD accompanied by diastolic dysfunction. Significant differences in functional capacity (p = 0.00) were found between each test group. Conclusion: There is a significant difference in functional capacity values between COPD groups with different severity and with or without diastolic dysfunction.